Lapatinib for advanced breast cancer overexpressing HER2 - Afonso, Sergio L.; Cataneo, Antonio José Maria [UNESP]; de Oliveira Carvalho, Paulo Eduardo (Wiley, 2016)
This is the protocol for a review and there is no abstract. The objectives are as follows: To evaluate the effectiveness and safety of lapatinib, used alone or in association with other drugs, improves the survival and the quality of life of woman with advanced breast cancer that overexpress the Human Epidermal Growth Factor Receptor 2 (HER2).